MONOMER REACTIVITY RATIOS OF CELLULOSE GRAFTED WITH N-CYCLOHEXYLACRYLAMIDE AND METHYL METHACRYLATE BY ATOM TRANSFER RADICAL POLYMERIZATION - Cankaya, Nevin; Temuz, M. Mursit (Editura Acad Romane, 2014)
The atom transfer radical polymerization (ATRP) of N-cyclohexylacrylamide (NCA) with methyl methacrylate (MMA) was performed in dimethylformamide (DMF) at 130 degrees C, in the presence of cellulose chloroacetate (Cell.ClAc) macro initiator, Cu(I)CI/2,2'-bipyridine catalytic system. The graft copolymers were characterized by elemental analysis, FT-IR spectra and thermal analysis. Thermal stabilities of the graft copolymers were determined by the TGA method and it was found that the thermal stability of the copolymers increased with the increase of MMA units, while it decreased with the increase of NCA units. In order to investigate the effect of NCA interactions with MMA monomers on grafting, graft copolymerization was also studied using different feed compositions, ranging from 0.15 to 0.85. The reactivity ratios of NCA and MMA by ATRP on cellulose were determined using the Finemann-Ross (F-R), inverted Finemann-Ross (inverted F-R), Yezrielev-Brolchina-Roskin (Y-B-R), Kelen-Tildos (K-T) and extended Kelen-Tudos (extended K-T) linearization methods. The reactive ratios of r(1) and r(2) were obtained to be 0.004-0.128 and 0.657-0.907, respectively; r(1).r(2) of the graft copolymers on cellulose is close to zero.
Keywords: cellulose; monomer reactivity ratios; ATRP; graft copolymer